An Introduction and Critical Review of the Methodology and Style of Tibyan-ul-Furqan by Allama Ghulam Rasool Saeedi - Muhammad Farooq; Dr. Mufti Muhammad Karim Khan (Journal of Religion and Society, 2025)
Allama Ghulam Rasool Saeedi’s methodological approach is characterized by the presentation of extensive evidences. He comprehensively discusses all relevant viewpoints on a given issue and finally identifies the preferred (rajih) opinion. His clear distinction between tafsir (exegesis) and ta’wil (interpretation) is a notable example of this balanced and scholarly method. In his renowned work Tibyan-ul-Furqan fi Tafsir al-Qur’an, Allama Saeedi not only highlights the significance of Hanafi jurisprudence but also provides a well-reasoned refutation of the atheistic and apostatic ideologies of modernists and atheists through strong arguments and evidences. His critical analysis of liberal interpretations concerning Hajj, ‘Umrah, and the sa ‘i between Safa and Marwah particularly the views of Ghulam Ahmad Parvez (d. 1985) demonstrates his commitment to defending orthodox Islamic teachings. In Tibyan-ul-Furqan, Allama Saeedi adopts a modern research-oriented methodology by applying the principles of Qur’anic exegesis as the criteria for the acceptance and rejection of exegetical narrations. This tafsir is not merely a summary of Tibyan al-Qur’an; rather, it contains numerous additional discussions and expanded scholarly analyses. Another distinctive feature of Allama Saeedi’s scholarship is that whenever he cites the statements of earlier Imams or scholars, he also mentions their year of death, a practice rarely observed among other exegetes. This rigorous academic style helps in understanding the historical context of the scholars and in identifying inconsistencies in contradictory reports. Furthermore, the systematic and comprehensive bibliography provided at the end of Tibyan-ul-Furqan reflects a high standard of academic research. The careful organization of references enhances the reader’s engagement, facilitates further study, and clearly demonstrates the author’s scholarly competence and intellectual depth. Keyword: Tibyan-ul-Furqan: Introduction, Methodology, Style, Analysis, Distinctive Features, and Critical Review